Dampak Pelatihan Pembuatan Toko Online Berbasis E-Commerce Dengan Metode Rapid Prototyping Bagi Siswa Sekolah Menengah Kejuruan - Pramudito, Dendy K. Pramudito; Prasetyo, Sutrisno Aji Prasetyo; Sunge, Aswan Supriyadi (Forum Kerjasama Pendidikan Tinggi, 2025)
Learning in e-commerce development is vital in helping understand digital business concepts, especially in overcoming the limitations of conventional learning methods, such as listening, observing, and taking notes. By using the ADDIE model, which includes analysis, design, development, implementation, and evaluation, this learning process provides a systematic and comprehensive approach. In this training, you will not only gain theoretical knowledge but also practical skills in modifying and managing e-commerce platforms. This learning aims to be able to understand and carry out the process of creating and managing an online business while stimulating creativity and enthusiasm for entrepreneurship. The results of this learning show that e-commerce development is very effective in facilitating the understanding of concepts and helping link theory to the world of work. Apart from that, the level of satisfaction of the female students was very significant, and they felt more prepared to apply the knowledge they had gained. This training proves that e-commerce development not only provides a better understanding of business but also prepares you with relevant skills to face the challenges of an ever-evolving digital world.